2011
DOI: 10.1145/2037676.2037684
|View full text |Cite
|
Sign up to set email alerts
|

Automatic creation of photo books from stories in social media

Abstract: Photos are a special way to tell stories of our best memories and moments. The representation of those photos in appealing physical photo books is highly appreciated by many people. Today, many photos are shared via social networking sites, where people upload their photos and share their stories with their friends. The members of social networks comment on each other's photos, add tags or descriptions and upload new photos of the same events to their albums. While the media of different personal events are av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 16 publications
0
43
0
Order By: Relevance
“…For example [2] introduced an unsupervised approach to cluster the photos to a known number of events using an expectation maximization algorithm, where the meta data, the content based and the camera based features were taken into account. More recently in [3] we also introduced an unsupervised algorithm that exploits social features as well as content features in the social networks in order to estimate the probabilistic relation between the photos. In the work of [4] the event was characterized in terms of four facets (Where, When, What, Who) and the user's social context was used to annotate photos because users do not always agree on annotations.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…For example [2] introduced an unsupervised approach to cluster the photos to a known number of events using an expectation maximization algorithm, where the meta data, the content based and the camera based features were taken into account. More recently in [3] we also introduced an unsupervised algorithm that exploits social features as well as content features in the social networks in order to estimate the probabilistic relation between the photos. In the work of [4] the event was characterized in terms of four facets (Where, When, What, Who) and the user's social context was used to annotate photos because users do not always agree on annotations.…”
Section: Related Workmentioning
confidence: 99%
“…Friends may attend the same events and upload photos of each others in different accounts. For example, in [3] we showed that a large proportion of Facebook users have a high percentage of their photos added by others. Thus, it is not easy to find all photos belonging to one event by browsing a single album or account.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…These sources can also being integrated while offering interfaces to retrieve the photos from there or to offer special ways of generating photo books implementing both, text and photos into a well arranged product as shown in [10].…”
Section: Images In Different Physical Storage Locationsmentioning
confidence: 99%